Analysis of the Publication Process in the Field of Road Accidents and Injuries and Visualization of its Scientific Structure - Afshin Hamdipour; Hashem Atapour; Fatemeh Ghasemzadeh (Tehran University of Medical Sciences, 2021)
Background and Aim: Road injuries are one of the most important public health problems and the leading cause of death and injury all over the world. The aim of this study is to investigate the trend of publication in the domain of road incidents and injuries and to visualize its scientific structure. Materials and Methods: The present study is of scientometric type, its method is cross-sectional, and it was done during the period of 2005-2018. A total of 6563 records of road accidents and injuries were selected as the statistical population. The data collection tool was the Web of Science database and the HistCite software was used to visualize the scientific structure. Results: The United States, Australia, and the United Kingdom ranked first to third with the production of 927, 700, and 651 documents, and the records of these three countries received 26373, 24447, and 23733 citations, respectively. Besides, the rank of road accidents and injuries for these countries were 89, 115, and 132, and the rate of casualties per 100,000 populations was equal to 10.6, 4.5, and 2.9. On the other hand, Libya, Thailand and Malawi (in South-Eastern Africa) are ranked first to third in the areas under study. The number of publications of these three countries was 5, 58 and 18, and their rank in document publications was 100, 34 and 65, respectively.  Conclusion: The relationship between rank in publications and rank in road accidents was negative and significant; countries with higher publications had a lower rank in road accidents and injuries. This indicates an inverse relationship between the number of publications and the number of road injuries; This means that as the number of publications in this field increases, the rank in injuries will improve. It seems that one of the factors that may be effective in reducing injuries and road accidents is the serious intervention of researchers to conduct research in this area in order to raising awareness and create a traffic culture for citizens.